Aerobic Exercise as a Tool to Improve Hippocampal Plasticity and Function in Humans: Practical Implications for Mental Health Treatment - Kandola, Aaron; Hendrikse, Joshua; Lucassen, Paul J.; Yücel, Murat (Frontiers in Human Neuroscience, 2016)
Aerobic exercise (AE) has been widely praised for its potential benefits to cognition and overall brain and mental health. In particular, AE has a potent impact on promoting the function of the hippocampus and stimulating neuroplasticity. As the evidence-base rapidly builds, and given most of the supporting work can be readily translated from animal models to humans, the potential for AE to be applied as a therapeutic or adjunctive intervention for a range of human conditions appears ever more promising. Notably, many psychiatric and neurological disorders have been associated with hippocampal dysfunction, which may underlie the expression of certain symptoms common to these disorders, including (aspects of) cognitive dysfunction. Augmenting existing treatment approaches using AE based interventions may promote hippocampal function and alleviate cognitive deficits in various psychiatric disorders that currently remain untreated. Incorporating non-pharmacological interventions into clinical treatment may also have a number of other benefits to patient well being, such as limiting the risk of adverse side effects. This review incorporates both animal and human literature to comprehensively detail how AE is associated with cognitive enhancements and stimulates a cascade of neuroplastic mechanisms that support improvements in hippocampal functioning. Using the examples of schizophrenia and major depressive disorder, the utility and implementation of an AE intervention to the clinical domain will be proposed, aimed to reduce cognitive deficits in these, and related disorders.